The association between body composition and overall survival in patients with advanced non-small cell lung cancer - Liang Fu; Haiming Ding; Liupei Mo; Xiaoyu Pan; Lijuan Feng; Shenglian Wen; Qiaoqing Lan; Liling Long (Scientific Reports)
Abstract Nutritional status is associated with prognosis in a variety of cancers. Studies analyzing the association between the measurements of skeletal muscle and adipose tissue obtained from Computerized Tomography (CT) images at the time of diagnosis of advanced non-small cell lung cancer (NSCLC) and overall survival (OS) are relatively few. Data from 425 patients diagnosed with advanced NSCLC between January 2016 and December 2017 were retrospectively analyzed, with an average follow-up of 15.3 months. To outline the patient’s chest CT plain image at the time of diagnosis,skeletal muscle and subcutaneous fat at the level of both thoracic vertebrae were quantified in terms of mass and quantity by the pectoral muscle index (PMI), pectoral muscle density (PMD), subcutaneous fat index (SFI), subcutaneous fat density (SFD), paravertebral muscle index (PVMI), and paravertebral muscle density (PVMD). The SFI value in the female survival group is significantly lower than that in the death group (P = 0.049), and the PVMI value in the overall survival group is significantly lower than that in the death group (P < 0.001). After adjusting for clinical variables such as gender, smoking status, clinical staging, degree of differentiation, and radiotherapy history, the multivariable Cox regression analysis showed that an increase in SFI significantly improves the overall survival rate of patients (Hazard Ratio [HR] = 1.410, 95% Confidence Interval [CI]: 1.042–1.908, P = 0.026). Conversely, a decrease in PVMD is significantly associated with improved overall survival and prognosis (HR = 0.762, 95% CI: 0.579–0.982, P = 0.048). No association was found between body mass index (BMI) and chest muscle status indicators and overall survival (P > 0.05). CT-measured body composition parameters provide precise prognostic information and are superior to BMI; an increased OS rate in advanced NSCLC is associated with a greater SFI and a lower PVMD.